Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T21:46:13+01:00
A) [-2/3-(-1,8) / (-1 1/5)]/ (-1/27)=
=[ -2/3 - (- 9/5 )/ (-6/5)] / (-1/27) =
= [ -2/3 - (-9/5)*(-5/6)] * (-27) =
= [ -2/3 -3/2] *(-27)=
= [ -4/6 - 9/6] *(-27)=
= [ -13/6)*(-27)=
= 117/2
= 58,5

b)-4,2 / (-2 1/3) / (-0,036) / (-25) / (-1/3)=
= -21/5 : (-7/3) : (-9/250): (-25) : (-1/3)=
= (-21/5)*(-3/7)*(-250/9)*(-1/25) *(-3) =
= (-10*3 ): 5=
= (-30) : 5 =
= -6
c)-(-0,006) / (-0,04)/ 1 1/5 * (-3,2) * 2 3/4 / (-2,2)=
= -(-3/500) : (-1/25) : 6/5 *(-16/5)*(11/4): (-11/5)=
= 3/500*(-25) *5/6*(-16/5)*11/4*(-5/11)=
= - 3/6 =
= - 1/2